The Effect of Visual Consistency and Content Quality on Online Purchase Intention Through Brand Awareness of The Local Fashion Brand Rangkay Future - Salman Haqil Majid; Edi Nurtjahjadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
Rangkay Future, a locally produced casual fashion brand based in Bandung, recorded 45.08% sales growth in 2024 before its revenue contracted by 38.85% through the third quarter of 2025, a reversal that raises questions about whether its digital brand communication still succeeds in converting audience exposure into purchase behavior. This study examines the effect of visual consistency and content quality on online purchase intention, with brand awareness positioned as a mediating variable, extending the stimulus-organism-response model of Dabbous and Barakat (2020) by introducing visual consistency as an additional cognitive stimulus alongside content quality. Data were collected from 111 social media users aged 17-34 in Bandung who had been exposed to Rangkay Future's Instagram content, selected through purposive sampling, and analyzed using multiple linear regression and the Sobel mediation test in IBM SPSS Statistics version 26. The results show that visual consistency and content quality each significantly increase brand awareness, that visual consistency and brand awareness each significantly increase online purchase intention, and that content quality has no significant direct effect on online purchase intention once brand awareness is accounted for. The Sobel test confirms that brand awareness fully mediates the effect of content quality on online purchase intention and partially mediates the effect of visual consistency. These findings indicate that, for an emerging local brand, informative content builds purchase intention only through the awareness it generates, whereas a consistent visual identity drives purchase intention both directly and through awareness.